1985
DOI: 10.1161/01.hyp.7.3_pt_2.i43
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atrial natriuretic factor on blood pressure, renin, and aldosterone in Goldblatt hypertension.

Abstract: SUMMARY We previously provided evidence that atrial natriuretic factor (ANF) antagonizes angiotensin H-induced vascular contractility and angiotensin H-stimulated aldosterone production by isolated adrenal cells. To examine the importance of these effects in vivo, synthetic ANF (auriculin A) was administered intravenously (2 M&^g bolus followed by 0.3 ^ug/kg/min constant infusion) to conscious, unrestrained two-kidney, one-clip and one-kidney, one-clip rats on normal sodium intake and their sham-operated contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 23 publications
(12 reference statements)
4
25
0
Order By: Relevance
“…In fact, the hind limb vasoconstriction is perhaps more easily explained as a reflex response secondary to the fall in systemic BP than as a direct vascular effect of ANF since following sympathetic receptor blockade the hind limb vascular response to the peptide is actually represented by a slight but consistent reduction. The lack of an associated reflex tachycardia might be accounted for by a concurrent vagomimetic effect of ANF, which has been already described with the crude atrial extract by Ackermann et al' 7 and which is demonstrated with the synthetic peptide in the present study (see below).…”
Section: Figure 4 Reflex Chronotropic Responses (A//pj (Mean ± Sem) supporting
confidence: 85%
See 1 more Smart Citation
“…In fact, the hind limb vasoconstriction is perhaps more easily explained as a reflex response secondary to the fall in systemic BP than as a direct vascular effect of ANF since following sympathetic receptor blockade the hind limb vascular response to the peptide is actually represented by a slight but consistent reduction. The lack of an associated reflex tachycardia might be accounted for by a concurrent vagomimetic effect of ANF, which has been already described with the crude atrial extract by Ackermann et al' 7 and which is demonstrated with the synthetic peptide in the present study (see below).…”
Section: Figure 4 Reflex Chronotropic Responses (A//pj (Mean ± Sem) supporting
confidence: 85%
“…The observation that bilateral vagotomy is able to prevent the fall in BP induced by ANF and the concurrent reflex vasoconstriction, while atropine and sympathetic receptor blockade are not, supports the hypothesis of Ackermann et al' 7 that ANF lowers BP mainly through a reflex effect of direct stimulation of cardiopulmonary receptors with vagal afferents. These authors postulated such an effect to explain the cardiovascular response to atrial extracts.…”
Section: Figure 4 Reflex Chronotropic Responses (A//pj (Mean ± Sem) supporting
confidence: 79%
“…The failure to demonstrate suppression of renin and aldosterone in recent clinical studies (13, 14,27) is probably attributable to the fact that measurements were performed under non-steady-state conditions and/or in supine subjects, in whom the renin-angiotensin-aldosterone axis is already relatively suppressed. It has been postulated that the ability ofANF to suppress renin secretion, whether or not direct effects on the juxtaglomerular cells are involved, may depend on an intact renal hemodynamic response to the peptide (36)(37)(38), and it has been shown that direct adrenal effects contribute to the aldosteronelowering effect ofANF in vivo under certain circumstances (36)(37)(38). Our studies do not provide further definition of the mechanisms involved but are consistent with these observations.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of plasma aldosterone levels in response to atrin infusion has also been documented in anesthetized dogs (12) and in conscious rats (96 (98), although a direct effect of atrin on renin secretion by renal cortical slices has also been reported (99). In conscious rats, plasma renin activity was only reduced in states where the renin-angiotensin system was chronically stimulated, as in two kidney-one clip Goldblatt hypertension, and in salt-deleted one kidney-one clip Goldblatt hypertensive rats (100). In normal rats and in rats with volumedependent hypertension (one kidney-one clip Goldblatt hypertension on a normal salt intake), atrin failed to alter plasma renin activity (100).…”
Section: Actions On Aldosterone Biosynthesis and Secretionmentioning
confidence: 99%
“…In conscious rats, plasma renin activity was only reduced in states where the renin-angiotensin system was chronically stimulated, as in two kidney-one clip Goldblatt hypertension, and in salt-deleted one kidney-one clip Goldblatt hypertensive rats (100). In normal rats and in rats with volumedependent hypertension (one kidney-one clip Goldblatt hypertension on a normal salt intake), atrin failed to alter plasma renin activity (100). Similarly, in conscious dogs with inferior vena cava ligation, a chronic hyperreninemic state, atrin markedly suppressed plasma renin activity, whereas no response was seen in normal dogs (101).…”
Section: Actions On Aldosterone Biosynthesis and Secretionmentioning
confidence: 99%